2014
DOI: 10.1063/1.4897345
|View full text |Cite|
|
Sign up to set email alerts
|

Height control of self-assembled quantum dots by strain engineering during capping

Abstract: Strain engineering during the capping of III-V quantum dots has been explored as a means to control the height of strained self-assembled quantum dots. Results of Kinetic Monte Carlo simulations are confronted with cross-sectional Scanning Tunnel Microscopy (STM) measurements performed on InAs quantum dots grown by molecular beam epitaxy. We studied InAs quantum dots that are capped by InxGa(1−x)As layers of different indium compositions. Both from our realistic 3D kinetic Monte Carlo simulations and the X-STM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…This shows that the values are over estimated. Indeed, the QDs height can be reduced by the capping process [ 29 , 30 ]. Additionally, the AFM technique may also provide an over estimated size due to the tip artifact [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the values are over estimated. Indeed, the QDs height can be reduced by the capping process [ 29 , 30 ]. Additionally, the AFM technique may also provide an over estimated size due to the tip artifact [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…2.7. In good agreement with the model proposed by Grossi et al [117], the QD height was found to follow a linear tendency with the Sb content, i.e., with the lattice parameter increase of the capping material.…”
Section: Modified Capping Layers (Cls)supporting
confidence: 90%
“…Contrarily an increase of the capping rate will kinetically restrain surface intermixing, facilitating the preservation of metastable QD structures and significantly increasing the aspect ratio. Remarkably, this is achieved even in a system with a high lattice mismatch between InAs QDs and GaAs CL (Δa~7%) without the use of strain-engineering strategies [117]. As observed in Fig.…”
Section: Fig 41mentioning
confidence: 76%
See 2 more Smart Citations